Data Security Using Textual and Graphical Approach for CAPTCHA (International Journal of Advanced Research in Science, Management and Technology, 2016)
Computer security depends largely on passwords in order to authenticate human users. The term password commonly refers to a secret used for authentication. Passwords are the most commonly used method for identifying users in computer and communication system. Graphical password schemes motivated by improving password usability and security. New graphical password schemes that exploit features of graphical input displays to achieve better security than text- based passwords. A password authentication system should encourage strong and less predictable passwords while maintaining security. Users have difficulty remembering a password that is long and random-appearing. Instead, they create short, simple, and insecure passwords. Graphical passwords have been designed to try to make passwords more memorable and easier for people to use and more secure. Using hard AI (Artificial Intelligence) problems for security initially is an exciting new paradigm. Under this paradigm, the most notable primitive invented is CAPTCHA. It satisfies both conflicting requirement that is, it is easy to remember and it is hard to guess. This requires recognizing an image and using the recognized object as cues to enter a password. In recognition-recall CaRP, a password is a sequence of some invariant points of objects. A method is proposed a new security using registered details with secured using generate CAPTCHA images. In the Registration Phase User will input the Password in Click Text Phase. After Click Text Phase User will we be navigated to further Phase where a set of a Mathematical and Logical questions will be displayed followed by an image CAPTCHA challenge. Other technique used on log in process then generated by grid and display the 0-9 numbers. Also, this process has completed on numbers are randomly shuffle.
Keywords: Graphical Password, Security primitive, Captcha, Textual Password, Password, ClickText, TextGrid